ANALISIS PENGARUH TQM TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan PT. Rimatex Putra Nusantara Wanarejan Taman, Pemalang) - Amarullah, Idris; Sudaryanto, Budi (Diponegoro Journal of Management, 2017)
TQM or Total Quality Management is a management strategy shown to instill a quality awareness on all processes within the organization. In accordance with the ISO definition, TQM is "a management approach for a quality-centered organization based on the participation of all its members and aims for long-term success through customer satisfaction and benefits for all members of the organization and society."This study uses leadership, commitment, strategic planning, and teamwork as independent variables and employee performance as a dependent variable. Population in this research is all employees of PT. Rimatex Putra Nusantara Wanarejan Taman Pemalang. The technique of semple taken is saturated sampling. With a semple number of 100 employees. The data obtained have been tested for reliability and validity by using validity and reliability test. The method used in this research is multiple linear regression analysis.Based on the results of multiple linear regression analysis showed that there is a positive and significant influence of leadership, commitment, strategic planning, and teamwork on employee performance. From the results of the coefficient of determination shows that leadership, commitment, strategic planning, and teamwork have an effect on the performance of employees of PT. Rimatex Putra Nusantara is 57% while the rest 43% is explained by other variable not explained in this research.